Examine The Behavior Of Private Universities Lecturer In Respecting Kampus Merdeka Policies Using Theory Of Planned Behavioral Approach - Purboyo; Zulfikar, Rizka; Lamsah; Syahrani; Vitria, Aida (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2021)
This study aims to examine the behavior of PTS lecturers in responding to the Merdeka Learning - Merdeka Campus policy using Theory Of Planned Behavioral (TPB). In this study, TPB was adopted to explain the behavior of private university lecturers in responding to the independent campus policy. The variables used in this study are perceptions, attitudes, subjective norms, interests, and behavior. The population was PTS lecturers with a total sample of 251 people and came from 21 private universities in Banjarmasin municipality with the sampling technique using purposive sampling. The data analysis techniques are quantitative descriptive and structural equation models. The results of this study include (1) the variable perception, attitude, subjective norms and interests, the percentage of high category responses > the number of percentage responses in the low category which means that the research sample gives more positive responses to the variables of perception, attitude, subjective norms, and interest, (2) As for the behavior variable, the percentage of responses in the high category < the number of the percentage of responses in the low category, which means that the research sample gave fewer positive responses to the variable behavior of lecturers in responding to the policy of the Independent Campus, (3) The structural equation model was in accordance Goodness Of Fit Index standards and can explain the use of the theory of Planned Of Behavioral in describing the relationship between perceptions of attitudes, subjective norms, interests, and behavior of lecturers in responding to the policy of Merdeka Belajar - Kampus Merdeka.